Peran Stategis Inovasi LPD Kerobokan dalam Meningkatkan Daya Saing UMKM Lokal - Ni Made Satya Utami; Ni Putu Julia Yustyeka Dewi; I Ketut Somawangsa Sogata; Ni Kadek Chery Marshela Dewita; I Made Suarsa (CV. ITTC INDONESIA, 2025)
This study employs a qualitative approach using direct observation and in-depth interviews to investigate the strategic role of innovation by Lembaga Perkreditan Desa (LPD) in enhancing the competitiveness of local UMKM in Bali. The research reveals that LPDs, particularly in Desa Adat Kerobokan, have implemented various product, technological, and institutional innovations. Programs such as Term Deposits, Time Savings, and Unsecured Loans (KTA), which are specifically designed to meet the real needs of local UMKM, facilitate the implementation of these innovations. In addition to improving access to capital, these innovations have enhanced productivity, entrepreneurial capacity, and business resilience in facing the challenges of digitalization and globalization. The success of LPD innovations is strongly influenced by a combination of internal factors such as the quality of human resources and managerial commitment and external factors such as the trust of traditional communities, local regulatory support, and synergy with the tourism sector. The findings affirm that LPDs are not merely financial institutions, but cultural-based agents of socio-economic transformation capable of promoting inclusive and sustainable development at the village level.